Documenta X : Short Guide. - Bamgboyé, Oladélé Ajiboyé; Ciret, Yan; David, Catherine; Funcke, Bettina; Heise, Volker; Hoffmann, Jens; Kramer, Brigitte; Lamunière, Simon; Lepecki, André; Mucha, Reinhard; Prinz, Suzanne; Sztulman, Paul; et al. (Kassel : Documenta und Museum Fridericianum, 1997)
Adams, Robert ; Althamer, Pawel ; Archigram ; Archizoom Association ; Art & Language ; Aya & Gal Middle East ; Bamgboyé, Oladélé Ajiboyé ; Baumann, Andreas ; Baumgarten, Lothar ; Beaugrand, Catherine ; Blank, Joachim ; Bonk, Ecke ; Broodthaers, Marcel ; Bunting, Heath ; Burnett, Charles ; Bustamante, Jean-Marc ; Clark, Lygia ; Coleman, James ; Collective (La Ciutat de la Gent) ; Craig, Stephen ; Crandall, Jordan ; Douglas, Stan ; van der Elsken, Ed ; Evans, Walker ; van Eyck, Aldo ; Fahlström, Öyvind ; Farocki, Harun ; Fischli & Weiss ; Friedl, Peter ; Friese, Holger ; Gillick, Liam ; Gob Squad ; Goebbels, Heiner ; Golz, Dorothee ; Graham, Dan ; Grand, Toni ; Graumann, Hervé ; Grimonprez, Johan ; Grossarth, Ulrike ; Haacke, Hans ; Hains, Raymond ; Hamilton, Richard ; Hapaska, Siobhán ; Hausswolff, Carl Michael von ; Heiman, Michal ; Herold, Jörg ; Hill, Christine ; Hohenbüchler, Christine & Irene ; Höller, Carsten ; Honetschläger, Edgar ; Huber, Felix Stephan ; Jeron, Karl Heinz ; Jodi ; Kelley, Mike ; Kentridge, William ; Kippenberger, Martin ; Kleiner, Danielle Vallet ; Koester, Joachim ; Kogler, Peter ; Konrad, Aglaia ; Koolhaas, Rem ; Kroesinger, Hans-Werner ; Lafont, Suzanne ; Landau, Sigalit ; Lassnig, Maria ; Lauwers, Jan ; Lerch, Antonia ; Levitt, Helen ; Marker, Chris ; Marshall, Kerry James ; Marthaler, Christoph ; Matta-Clark, Gordon ; McQueen, Steve ; Milev, Yana ; Mosler, Mariella ; Moulène, Jean-Luc ; Mucha, Reinhard ; Müller, Christian Philipp ; Mullican, Matt ; Muntadas, Antoni ; Ngui, Matthew ; Nicolai, Carsten ; Nicolai, Olaf ; Noll, Udo ; Nordey, Stanislas ; Oiticica, Hélio ; Orozco, Gabriel ; Oursler, Tony ; Page, Adam ; Pataut, Marc ; Peck, Raoul ; Peljhan, Marko ; Pistoletto, Michelangelo ; Pittman, Lari ; etc.
biog.
Documenta X, Kassel, 21. Juni bis 28. September 1997
Engels & Duits
boek